A Synergistic Botanical Compound Preparation of Ganoderma lucidum, Lycium ruthenicum, and Red Ginseng Alleviates Exercise-Induced Fatigue via Coordinated Regulation of Energy Metabolism, Oxidative Stress, and Gut Microbiota in Mice - Tao Liu; Mengmin Li; Wanyun Xu; Zhenhao Li; Yuanxiang Jin; Ting Luo; Tao Ma; Jintao Cheng; Shiyu Li; Qingchi Wang; Kan Shao; Yi Yang; et al. (Food Bioscience, 2026)

Plant-derived exosome-like nanoparticles – from Laboratory to factory, a landscape of application, challenges and prospects - Chaozhi Wei; Mengyu Zhang; Jintao Cheng; Jinzhong Tian; Guiling Yang; Yuanxiang Jin (Critical Reviews in Food Science and Nutrition, 2025)

Genetically engineered Bacillus subtilis-derived extracellular vesicles Alleviates Ulcerative colitis by restoring intestinal barrier and regulating gut microbiota - Jiali Chen; Chaozhi Wei; Chunqiang Pan; You Wei; Baoxian Li; Tao Liu; Xiao Wang; Zhengshun Wen; Yao Zhao; Mengyu Zhang; Jintao Cheng; Yuanxiang Jin; et al. (Chemical Engineering Journal, 2025)

Joint toxic effects of thiamethoxam and flusilazole on the adult worker honey bees (Apis mellifera L.) - Dou Wang; Lu Lv; Zhongwen Gao; Yu-Cheng Zhu; Hongbiao Weng; Guiling Yang; Yanhua Wang (Environmental Pollution, 2023)

Dissolved Nitrous Oxide and Hydroxylamine in the South Yellow Sea and the East China Sea During Early Spring: Distribution, Production, and Emissions - Xueji Gu; Fang Cheng; Xiaolei Chen; Guanxiang Du; Guiling Zhang (Frontiers in Marine Science, 2021)
Coastal marine systems are active regions for the production and emission of nitrous oxide (N 2 O), a potent greenhouse gas. Due to the inherently high variability in different coastal biogeochemical cycles, the factors and mechanisms regulating coastal N 2 O cycling remain poorly understood. Hydroxylamine (NH 2 OH), a potential precursor of N 2 O, has received less attention than other compounds in the coastal areas. Here, we present the spatial distribution of N 2 O and the first reported NH 2 OH distribution in the South Yellow Sea (SYS) and the East China Sea (ECS) between March and April 2017. The surface N 2 O concentrations in the SYS and the ECS varied from 5.9 to 11.3 nmol L –1 (average of 8.4 ± 1.4 nmol L –1 ) and were characterized by offshore and north–south decreasing gradients. NH 2 OH showed patchy characteristics and was highly variable, fluctuating between undetectable to 16.4 nmol L –1 . We found no apparent covariation between N 2 O and NH 2 OH, suggesting the NH 2 OH pathway, i.e., nitrification (ammonium oxidation), was not the only process affecting N 2 O production here. The high NH 2 OH values co-occurred with the greatest chlorophyll- a and oxygen levels in the nearshore region, along with the relationships between NO 2 – , NO 3 – , and NH 2 OH, indicating that a “fresh” nitrifying system, favoring the production and accumulation of NH 2 OH, was established during the phytoplankton bloom. The high N 2 O concentrations were not observed in the nearshore. Based on the correlations of the excess N 2 O (ΔN 2 O) and apparent oxygen utilization, as well as ΔN 2 O vs. NO 3 – , we concluded that the N 2 O on the continental shelf was mainly derived from nitrification and nitrifier denitrification. Sea-to-air fluxes of N 2 O varied from −12.4 to 6.6 μmol m –2 d –1 (−3.8 ± 3.7 μmol m –2 d –1 ) using the Nightingale et al. (2000) formula and −13.3 to 6.9 μmol m –2 d –1 (−3.9 ± 3.9 μmol m –2 d –1 ) using the Wanninkhof (2014) formula, which corresponds to 75–112% in saturation, suggesting that the SYS and the ECS acted overall as a sink of atmospheric N 2 O in early spring, with the strength weakening. Our results reveal the factors and potential mechanisms controlling the production and accumulation of NH 2 OH and N 2 O in the SYS and the ECS during early spring.

West African monsoon decadal variability and surface-related forcings: second West African Monsoon Modeling and Evaluation Project Experiment (WAMME II) - Yongkang Xue; Fernando De Sales; William K.-M. Lau; Aaron Boone; Kyu-Myong Kim; Carlos R. Mechoso; Guiling Wang; Fred Kucharski; Kathleen Schiro; Masahiro Hosaka; Suosuo Li; Leonard M. Druyan; et al. (Climate Dynamics, 2016)

SIRT1 activation by pterostilbene attenuates the skeletal muscle oxidative stress injury and mitochondrial dysfunction induced by ischemia reperfusion injury - Yedong Cheng; Shouyin Di; Chongxi Fan; Liping Cai; Chao Gao; Peng Jiang; Wei Hu; Zhiqiang Ma; Shuai Jiang; Yushu Dong; Tian Li; Guiling Wu; et al. (Apoptosis, 2016)

Large-scale analysis of protein phosphorylation in Populus leaves - Jinwen Liu; Deli Ning; Guiling Zhao; Yuxiang Cheng; Baichen Wang (Journal of Plant Biochemistry and Biotechnology, 2014)

Integrating miRNA and mRNA expression profiles in response to heat stress-induced injury in rat small intestine - Jin Yu; Fenghua Liu; Peng Yin; Xiaoyu Zhu; Guiling Cheng; Nin Wang; An Lu; Weili Luan; Nuowei Zhang; Jiefeng Li; Kaijun Guo; Yulong Yin; et al. (Functional & Integrative Genomics, 2011)